Comparison of Novel Acoustic Rain Sensor Field Data with Co-located Tipping Bucket Rain Gauge - Domer, Prince Aldrin (Archīum Ateneo, 2019)
Gathered data on novel acoustic rain sensors deployed from June to November 2017 in four sites in the Philippines were analyzed and compared to co-located tipping bucket rain gauges. The behavior and performance of the acoustic rain sensors vis-à-vis the tipping buckets were understood through visualizations of the acoustic power levels and computed rain rates, and omnibus and post-hoc tests i.e. one-way ANOVA and Tukey test. Mean acoustic power levels were shown to have positive correspondence with rain intensity, but is subject to ambient noise and automatic gain control (AGC) in certain rain events. The findings of this study forwards recommendations on design improvements for future iterations of the sensor development and field deployment.